VICKERS, Peter, Understanding Inconsistent Science, Oxford, Oxford University Press, 2013. - Molina Oltra, Miquel Maria (Daimon Revista Internacional de Filosofia, 2015)
Reseña de Vickers, Peter, Understanding Inconsistent Science, Oxford, Oxford University Press, 2013.